2013
DOI: 10.1177/0003319713494753
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is a Risk Factor for Significant Carotid Atherosclerosis in Patients Aged 39 to 55 Years

Abstract: We compared the prevalence of risk factors between young and old individuals with significant carotid atherosclerosis. We retrospectively reviewed the records of patients aged 39 to 55 years (group I) and aged ≥ 60 years (group II) with significant atherosclerotic stenosis at the carotid bifurcation. Group I patients had significantly higher values for the following factors: weight, height, body mass index, diastolic pressure, prevalence of current smoking, total and low-density lipoprotein cholesterol and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Our results indicate that age, gender, and diabetes significantly affect the prevalence of CA. Other studies reported hypercholesterolemia, 18 obesity, 19 hypertension, 20 and other factors to be additional risk factors associated with CA. However, as shown in this study, these factors were only associated with the prevalence of CA in either men or women and showed no significant correlation with the prevalence of CA in the overall population.…”
Section: Discussionmentioning
confidence: 94%
“…Our results indicate that age, gender, and diabetes significantly affect the prevalence of CA. Other studies reported hypercholesterolemia, 18 obesity, 19 hypertension, 20 and other factors to be additional risk factors associated with CA. However, as shown in this study, these factors were only associated with the prevalence of CA in either men or women and showed no significant correlation with the prevalence of CA in the overall population.…”
Section: Discussionmentioning
confidence: 94%
“…[51] In another study, higher BMI was a risk factor for significant carotid atherosclerosis (higher rate of occlusion and near occlusion) in the patients aged 39 to 55 years. [52]…”
Section: Discussionmentioning
confidence: 99%
“…Khambet et al (8) reported values for sensitivity of 76% and specificity of 99% for DPR detecting calcified carotid artery atheromatous plaques. With this in mind we aimed to analyse the relation The risk factors for atherosclerosis, according to the literature, coincide with cardiovascular disease (13), such as increasing age (14), history of stroke, hypertension, diabetes, smoking, hypercholesterolemia (1,6,9,11,12,14), alcohol consumption (4,15) and obesity (16). Zheng et al (15) reported statistical significance between alcohol consumption in a population with atherosclerosis and cardiovascular accidents.…”
Section: Discussionmentioning
confidence: 99%